2006
DOI: 10.1111/j.1468-2982.2006.01225.x
|View full text |Cite
|
Sign up to set email alerts
|

Headache Patients in Primary Care and a Tertiary Care Unit in Zürich, Switzerland

Abstract: The Headache and Pain Clinic (HPC) is a unit of the Zürich Neurology Department, established in 1966. In the present study demographic features, clinical characteristics and medical management of primary and tertiary care patients were compared in two groups of 181 patients each, seen by general practitioners (GPs) or the HPC, respectively, for primary headaches in 1998. There was a preponderance of women and the socially underprivileged in both samples. Chronic headache was overrepresented in the HPC (44.7%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
0
9
0
2
Order By: Relevance
“…Approximately 40% of patients with M and PM were satisfied with alternative methods, whereas in the TTH group this percentage was even higher, at 60%. Studies from other countries show that patients relatively frequently reach for alternative methods for headache treatment: approximately one-third of patients in Italy, Switzerland, and Singapore tried at least one method [25, 36, 37]. Analysis of patients who visited a specialized headache clinic revealed that even 84% tried one or more alternative methods and 60% of those stated that these methods were efficient [38].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 40% of patients with M and PM were satisfied with alternative methods, whereas in the TTH group this percentage was even higher, at 60%. Studies from other countries show that patients relatively frequently reach for alternative methods for headache treatment: approximately one-third of patients in Italy, Switzerland, and Singapore tried at least one method [25, 36, 37]. Analysis of patients who visited a specialized headache clinic revealed that even 84% tried one or more alternative methods and 60% of those stated that these methods were efficient [38].…”
Section: Discussionmentioning
confidence: 99%
“…In studies from Europe, prevalence of CDH ranged from 27% to 60% at the tertiary care [5][6][7] . The diagnosis frequency had changed significantly among the CDH between the two assessments, although the absolute number remain relatively stable -n=45 in 2007 and n=41 in 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Around 87% of the patients had some form of migraine both in the first and second assessments. Other studies conducted at the tertiary care found that the prevalence of migraine at this setting ranges from 33 to 80% [3][4][5][6]8 . A past study conducted in our clinic diagnosed migraine in 79.2% of the patients 3 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations